Massive atrial myxoma presenting with unexplained haemoptysis. Issue 4 (29th April 2022) - Tsagkridi, Aliki; Keenan, Niall; Keramida, Kalliopi; Anderson, Jonathan
Abstract : Cardiac myxomas are scarce and their clinical manifestations can often be misdiagnosed or confused with other medical conditions. However, early diagnosis and surgical resection can prevent devastating complications of myxomas. We herein describe a case of a huge left atrial myxoma of a female patient in her late 30s. What makes our case unique, apart from the massive size of the myxoma, is the unusual clinical presentation with incessant cough and haemoptysis for more than 6 months. The diagnosis was made by echocardiography and cardiac MR and successful surgical resection was performed with good long-term outcome.